Information Technology and Rural Development in India - Nirvikar Singh (University of California, Economics Department, 2004)
How can information technology (IT) contribute to rural development? What are the channels through which impacts can be realized, and what are the practical means for realizing potential benefits? This paper examines several ongoing projects that aim to provide IT-based services to rural populations in India. These projects are distinguished by the goal of commercial sustainability, which supports scalability and, therefore, more widespread benefits. The analysis highlights the common building blocks required for successful implementation, and the relative strengths and weaknesses of different approaches.
Keywords: 330; India; information technology; Internet; rural development